Pengendalian Kelembaban Tanah dan Suhu Dalam Green House - Eva I. Mahaganti; Sherwin R.U.A. Sompie; Feisy D. Kambey; Reynold F. Robot (Jurnal Teknik Elektro dan Komputer, 2019)
Abstract — Green house is one way to cultivate plants to protect plants from rain, maximize photosynthesis and protect from disturbing plant pests. System was build green houses with controlled soil moisture and temperature in accordance with the conditions needed by shallots. System uses YL-69 soil moisture sensor, DHT22 temperature sensor, the data acquisition process using Arduino nano to control soil moisture using on-off controllers and the temperature uses proportional controlersl. If often exposed to sunlight, it provides a very significant change in soil moisture in plant pots, and at green house the maximum temperature is 39°C and minimum temperature is 24°C. Keywords — Arduino Nano; DHT22 Temperature Sensor; Green House; On-Off Controller; Proportional Controller; YL-69 Soil Moisture Sensor. Abstrak — Green house termasuk salah satu cara membudidayakan tanaman untuk melindungi tanaman dari hujan, memaksimalkan proses fotosintesis dan melindungi dari hama tanaman yang mengganggu. Dibuat sistem untuk membangun green house dengan kelembaban tanah dan suhu yang terkendali sesuai dengan kondisi yang dibutuhkan bawang merah. Sistem menggunakan sensor kelembaban tanah YL-69, sensor suhu DHT22, proses akuisisi datanya menggunakan arduino nano, mengendalikan kelembaban tanah menggunakan pengendali on-off  dan suhu dalam green house menggunakan pengendali proporsional. Jika sering terpapar sinar matahari maka perubahan yang sangat signifikan terhadap kelembaban tanah di dalam pot tanaman. Dalam green house diperoleh suhu maximum 39°C dan suhu minimum 24°C.Kata kunci — Arduino Nano; Green House; Pengendali On-Off; Pengendali Proporsional; Sensor Kelembaban Tanah YL-69; Sensor Suhu DHT22.